Удосконалення технології продуктів молоковмісних кисломолочних з поліфункціональними наповнювачами природного походження - Белемець, Тетяна Олександрівна (My University, 2021)
Дисертаційна робота присвячена удосконаленню технологій молоковмісних кисломолочних продуктів шляхом розробки і застосування науково-обґрунтованого купажу рослинних олій. Згідно проведених теоретичних та експериментальних досліджень здійснено обґрунтування удосконалених технологій молоковмісних кисломолочних продуктів: пасти молоковмісної сиркової з обліпихою та соусу молоковмісного сметанного з часником та цибулею. За встановленими критеріями обґрунтовано вибір натуральних рослинних олій – волоського горіху, ріпакової та кукурудзяної для подальшого використання у вигляді купажу в технологіях пасти молоковмісної сиркової та соусу молоковмісного сметанного; визначена можливість 50 %-ї заміни масової частки молочного жиру у складі молоковмісних кисломолочних продуктів на створений купаж натуральних рослинних олій; розроблено спеціальну математичну програму у середовищі «MatLab» для здійснення оптимізації жирнокислотного складу купажу рослинних олій; встановлено, що за умови заміни 50 %-в молочного жиру у складі пасти молоковмісної сиркової та соусу молоковмісного сметанного, співвідношення між насиченими,мононенасичени-ми та поліненасиченими жирними кислотами, а також жирними кислотами родин ɷ – 6 : ɷ – 3 – знаходяться у межах рекомендованих дієтологами норм. Обґрунтовано вибір емульгатору натурального походження – жовткового порошку, для розроблення ефективних емульсій на основі купажу та визначено доцільну кількість його введення; встановлено рекомендоване співвідношення компонентів у складі рослинної емульсії; визначено раціональні технологічні параметрами отримання рослинних емульсій. Обґрунтовано спосіб та визначені етапи підготовки сухого листя стевії; встановлені раціональні технологічні параметри отримання солодкого екстракту стевії з використанням роторно-імпульсного апарату; доведено, що використання молочної сироватки у якості екстрагенту дозволяє збільшити ступінь вилучення цільового компоненту з сухого листя стевії. Визначено рекомендований вміст смако-ароматичних наповнювачів у складі молоковмісних кисломолочних продуктів. Досліджено антибактеріальну та бактеріостатичну дії композиційної суміші часнику та цибулі по відношенню до типових контамінантів кисломолочних продуктів, що ймовірно обумовлене вмістом фітонцидів та фітоалексинів у їх складі. Досліджено показники безпеки молоковмісних продуктів за кислотним та пероксидним числами. Визначено фізико-хімічні показники пасти молоковмісної сиркової з обліпихою та соусу молоковмісного сметанного з композиційною сумішшю часнику та цибулі; обґрунтовано рекомендовані терміни їх зберігання. Розроблено нормативну документацію на удосконалені технології молоковмісних кисломолочних продуктів та здійснено промислову апробацію на ТОВ “Деражнянський молочний завод”, що підтверджується актами і протоколами виробничої перевірки. The dissertation is devoted to the improvement of technologies of milk - containing products by development and application of scientifically substantiated blending of vegetable oils. The expediency of using natural plant raw materials as multifunctional fillers of natural origin in the technology of dairy products has been proved. According to the established criteria, the choice of natural vegetable oils – walnut oil, rapeseed and corn for further use in the form of a blend in the technology of milk-cheese curd paste and milk-sour cream sauce is justified. In accordance with a number of experimental studies, the possibility of 50% replacement of the mass fraction of milk fat in milk products by a blend of natural vegetable oils has been determined. A special mathematical program has been developed in the “MatLab” environment to optimize the fatty acid composition of a blend of vegetable oils. According to the results of mathematical calculations, the percentage of selected vegetable blend oils according to the recommended by nutritionists ratios of the three main groups of fatty acids, as 1: 1: 1 and fatty acids of the family ɷ – 6: ɷ – 3, as 6: 1 – should consist of: 36,62 % walnut oil, 33,96 % rapeseed oil and 29,42 % corn oil. According to the results of chromatographic analysis of the fatty acid composition of milk-cheese curd paste with 50% replacement of the mass fraction of milk fat by the developed blend of vegetable oils, compared with the control sample (milk fat) marked decrease in saturated fatty acids by 30,2 %, increase in monounsaturated fatty acids by 4,6% and an increase in polyunsaturated by 25,5 %. The composition of the fat phase of milk sour cream sauce, compared to the control sample, was changed to reduce the amount of saturated fatty acids by 33 % and increase the amount of monounsaturated and polyunsaturated fatty acids by 6,4 % and 26,6 %, respectively. It is established that under the condition of replacement of 50 % of milk fat in the composition of milk-containing curd paste and milk-sour cream sauce, the ratio of fatty acids of the families ɷ – 6: ɷ – 3 - are within the norms recommended by nutritionists, namely: 6,1: 1 and 6,2: 1, respectively. The choice of emulsifier of natural origin - yolk powder, for the development of effective emulsions based on blends is substantiated and the appropriate amount of its introduction is determined – 3 % (by weight of the blend). The rational ratio of components in the composition of the plant emulsion - aqueous phase: fat phase: emulsifier, as 21: 76: 3, has been experimentally established. A mathematical model of the process of emulsion formation in the form of a two-dimensional polynomial of the second degree is developed, which illustrates the dependence of the size of fat balls of emulsions on the speed of rotation of the working body of the emulsifier and processing time. Rational technological parameters of obtaining vegetable emulsions are: 2500 rpm, for the duration of processing – 3… 3,5 min, which ensures the achievement of the average size of fat globules 1,6 ± 0,2 micrometers. It was determined that in order to obtain an extract from dry stevia leaves, it is expedient to grind it to a particle size of 3,9 ± 0,1 mm of leaves, and to use a hydraulic module – 1:15. It is proved that the use of whey as an extractant allows to increase the degree of extraction of the target component from the dried leaves of stevia by 12,1 % compared with the use as an extractant – water. Technological parameters of stevia extract production are scientifically substantiated: temperature – 80 ± 5 ºС, for processing duration – 25… 30 min, for extraction of 3,1… 3,4 % of extractive substances. It is substantiated that the use of a rotary-pulse apparatus for obtaining an extract from stevia leaves allows to increase the degree of extraction of extractives from 0,1 to 0,4 %; rational technological parameters of stevia extract production using a rotary-pulse apparatus: temperature – 85 ± 5 ºС, with exposure – 20… 25 min, which provides the maximum amount of extraction of extractives - 3,4… 3,5 %. Based on the research, a rational percentage of flavoring agents in milk products was determined: stevia extract – 0,25 %, sublimated sea buckthorn powder – 4 %, garlic mixture 0,2 % and green onion – 1 %. It was investigated that the developed mixture of garlic and green onions has antibacterial and bacteriostatic properties, in particular the survival rate of the test culture of Bacillus subtilis relative to the initial concentration of cells (1,4×106 cfu/g) was: 1-st day of storage – 30 %, 7-th day – 45 %, 14-th day – 51 % and the 21-st day of storage – 60 %; there is a decrease in the survival rate of the test culture of Micrococcus albus relative to the initial concentration of cells (8,5×105 cfu/g): on the 1st day of storage – 17 %, on the 7-th – 14 %, on the 14-th – 10 % and on the 21-st day of storage – 10 %. The safety indicators of dairy products by acid and peroxide numbers have been studied. It was found that at the time of reaching the shelf life of the sample of milk-containing curd paste with sea buckthorn (14th day), the value of acid number was – 0,32 mgKOH/h, peroxide – 2,3 PN, mmol 1/2O/ kg. The values of peroxide and acid numbers of the sample of milk sour cream sauce with a composite mixture of garlic and onion (on the 21st day) were respectively: 2,2 mmol 1/2O/ kg and 0,3 mgKOH/h. Physico-chemical parameters of milk-containing curd paste with sea buckthorn and milk-sour cream sauce with a composite mixture of garlic and onion were determined, their shelf life was determined at 4 ± 2 ºС: not more than 7 days - for milk-containing curd paste with sea buckthorn and not more days - for milk sour cream sauce with a composite mixture of garlic and onion. Normative documentation has been developed: TU U 15.5-02070938-296: 2021 "Milk-containing cheese paste with sea buckthorn", TU U 15.5-02070938-295: 2021 "Milk-sour cream sauce with garlic and onion" and technological instructions for their production. Technologies of milk-cheese curd paste with sea buckthorn and milk-sour cream sauce with a composite mixture of garlic and onion were tested at Derazhnyansky Dairy Plant LLC, which is confirmed by acts and protocols of production inspection. The calculations of economic efficiency of production of the developed recipes are carried out: the approximate cost of 1 ton of milk-containing cheese paste with sea buckthorn is 247620.33 UAH, milk-sour cream sauce with a composite mixture of garlic and green onions is 543579.14 UAH. The cost of packaging a finished product weighing 100 g will be approximately UAH 24.8 for milk-containing curd paste with sea buckthorn, and for milk-sour cream sauce with a compositional mixture of garlic and onion – UAH 54.4. The production of the developed milk curd paste with sea buckthorn and milk sour cream sauce with garlic and onion is quite profitable and slightly more expensive than the basic production of milk products, and therefore should be made in small quantities as a healthy food.
Keywords: кафедра біотехнології і мікробіології; молоковмісні продукти; купаж рослинних олій; жирнокислотний склад; рослинні емульсії; жовтковий порошок; екстракт стевії; сублімований порошок обліпихи; milk products; blend of vegetable oils; fatty acid composition; vegetable emulsions; yolk powder; stevia extract; freeze-dried sea buckthorn powder